"Smoking Is Sóóó ... Sandals and White Socks": Co-Creation of a Dutch Anti-Smoking Campaign to Change Social Norms. Issue 5 (4th May 2017) - van den Heerik, Romy A. M.; van Hooijdonk, Charlotte M. J.; Burgers, Christian; Steen, Gerard J.
Abstract: This article considers co-creation as a new persuasive strategy in health campaigns. Co-creation enables target audience members to become active campaign producers. A recent Dutch anti-smoking campaign applied co-creation, inviting the target audience to complete the slogan "smoking is sóóó . . . " with something outdated on social networking sites (SNSs) like Facebook and Twitter to stress non-smoking as the new social norm. From a corpus-linguistic perspective, we investigated how the slogans from the target audience resonated with or deviated from the campaign's original message. In general, the target audience slogans followed the campaign's approach, but on the SNSs, differences were found regarding the valence, type of utterance, and domain to which smoking was compared. The target audience frequently compared smoking with other (inter)personal social norms. Co-creation thus provides the target audience with an opportunity to disseminate campaign messages from their own perspective, but at the same time a co-creation strategy risks diluting the intended campaign message.